CHALLENGES FACED BY THE ONE HEALTH APPROACH IN THE DEVELOPING COUNTRIES: AN INDIAN CASE STUDY (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT:The COVID-19 pandemic has starkly exposed the urgent need for enhanced collaboration among the realms of human, animal, and environmental health in combating zoonotic diseases. In countries like India, where the threat of zoonoses looms large, this imperative is especially pronounced. Despite widespread acknowledgment of this necessity, governments across the globe have grappled with effectively organizing their responses to this multifaceted challenge. To delve deeper into this issue, a comprehensive study was conducted, employing a combination of document analysis and interviews, focusing on the approaches of India, Bangladesh, Kenya, and Rwanda in managing zoonotic diseases.